Application of corneal tomography before keratorefractive procedure for laser vision correction. Issue 5 (15th April 2016) - Luz, Allan; Lopes, Bernardo; Salomão, Marcela; Ambrósio, Renato
Abstract : Ectasia after refractive surgery represents a major concern among refractive surgeons. Corneal abnormalities and preexisting corneal ectasia are the most important risk factors. Corneal topography and central corneal thickness are the factors traditionally screening for in refractive surgery candidates. Study of the anterior surface by Placido topography allows for identification of keratoconus before biomicroscopy. However, this is insufficient for the evaluation of pre‐operative refractive surgery. There are cases of ectasia after laser in situ keratomilusis (LASIK) without identifiable risk factors such that there is a need to go beyond the corneal surface. A key requirement is quantifying susceptibility to corneal biomechanical instability and progression to ectasia. Tomographic indices derived from elevation maps and pachymetry spatial variation produce a Belin Ambrosio display final D index (BAD‐D index), which has shown better results compared to surface curvature indices for detecting very mild forms of ectasia. A logistic regression formula, integrating age, residual stromal bed, and BAD‐D (Ectasia Susceptibility Score, ESS) resulted in a significant improvement in accuracy, leading to 100% sensitivity and 94% specificity for detecting susceptible cases. A comprehensive corneal structural analysis based on corneal segmental tomography can detect susceptible corneas, which increases safety for refractive surgery patients. Abstract : Ectasia after refractive surgery is among the complications most feared by surgeons. The presence of ectatic disease in the preoperative state is the main risk factor for ectasia. A 'traditional' evaluation is insufficient because there have been several cases of ectasia post‐ laser‐assisted in situ keratomilusis (LASIK) surgery without any identified risk factor. A comprehensive corneal structural analysis based on corneal tomography can detect susceptible corneas with very mild, subtle disease. The Ectasia Susceptibility Score (ESS) is new tool for preoperative evaluation, with significantly improved accuracy for detecting susceptible cases.